2014
DOI: 10.1152/ajpendo.00100.2014
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria: a possible nexus for the regulation of energy homeostasis by the endocannabinoid system?

Abstract: Lipina C, Irving AJ, Hundal HS. Mitochondria: a possible nexus for the regulation of energy homeostasis by the endocannabinoid system?.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 165 publications
(198 reference statements)
3
25
0
3
Order By: Relevance
“…(5) Enhanced lipoprotein lipase (LPL) activity stimulates G-protein-coupled receptors 40 and 120. These mechanisms are, in general, comparable to those described in mammals (Blouet and Schwartz, 2010;Lipina et al, 2014;Morton et al, 2014;Magnan et al, 2015) with the notable exception of the ability of fish systems to detect changes in the levels of not only LCFAs but also mediumchain fatty acids like octanoate (rainbow trout) and polyunsaturated fatty acids like α-linolenate (Senegalese sole). The activation of these systems results in an increase in the anorexigenic potential (balance between mRNA abundance of anorexigenic and orexigenic neuropeptides) through increased production of the anorexigenic peptides pro-opio melanocortin (POMC) and cocaine-and amphetamine-related transcript (CART) and decreased production of the orexigenic peptides neuropeptide Y (NPY) and agouti-related peptide (AgRP), ultimately leading to decreased food intake (Librán-Pérez et al, 2012, 2014Velasco et al, 2016a).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…(5) Enhanced lipoprotein lipase (LPL) activity stimulates G-protein-coupled receptors 40 and 120. These mechanisms are, in general, comparable to those described in mammals (Blouet and Schwartz, 2010;Lipina et al, 2014;Morton et al, 2014;Magnan et al, 2015) with the notable exception of the ability of fish systems to detect changes in the levels of not only LCFAs but also mediumchain fatty acids like octanoate (rainbow trout) and polyunsaturated fatty acids like α-linolenate (Senegalese sole). The activation of these systems results in an increase in the anorexigenic potential (balance between mRNA abundance of anorexigenic and orexigenic neuropeptides) through increased production of the anorexigenic peptides pro-opio melanocortin (POMC) and cocaine-and amphetamine-related transcript (CART) and decreased production of the orexigenic peptides neuropeptide Y (NPY) and agouti-related peptide (AgRP), ultimately leading to decreased food intake (Librán-Pérez et al, 2012, 2014Velasco et al, 2016a).…”
Section: Introductionsupporting
confidence: 67%
“…The orexigenic effect of ceramides is mediated by changes in fatty acid-sensing mechanisms (Gao et al, 2013;Lipina et al, 2014;Picard et al, 2014), integrative sensors such as AMP-activated protein kinase (AMPK) and sirtuin-1 (SIRT-1) (Gao et al, 2011;Ramírez et al, 2013), and cellular signalling pathways such as those mediated by protein kinase B (Akt), target of rapamycin (mTOR) and forkhead box protein O1 (FoxO1) (Bikman and Summers, 2011;Lipina et al, 2014). In fish, the few studies available demonstrated the presence of ceramides in brain (Duan et al, 2010) and their role in development (Fenderson et al, 1992) and apoptosis (Yabu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic disturbances such as diabetes and obesity are associated with altered mitochondrial respiratory function [60,61]. Importantly, endocannabinoids have been found to modulate mitochondrial morphology and membrane permeability [62]. AEA promotes mitochondrial swelling and membrane fluidity but downregulates cytochrome release and membrane potential [63,64].…”
Section: Mitochondrial Modulation By Cb Signalingmentioning
confidence: 99%
“…Notably, these effects are rescued by a peripheral blockade of CB 1 R, 9 in agreement with reports by others who describe a role for the eCB/CB 1 R system in modulating different aspects of mitochondrial physiology. [18][19][20][21] However, direct modulation of mitochondrial dynamics by eCBs has not yet been described. Here, we show that directly stimulating CB 1 R modulates mitochondrial dynamics and function in RPTCs.…”
Section: Introductionmentioning
confidence: 99%